Nineteenth century: Process of the Peruvian literature and the need to reconsider the situation of the others in the national scene - Huárag Álvarez, Eduardo (2016)
The purpose of this article is to contribute to a better understanding of the most important literary trends in the Peruvian cultural scenery of the nineteenth century. Costumbrismo is assumed as the reaffi rmation of our national identity (our customs, our social and cultural reality) against the others (the Spaniards). However, in the following decades, during romanticism, Peruvian creoles and intellectuals did not attempt an approach to the others (that is, to the Andean population and the rural reality of the country). Only after the war against Chile and with the exceptional participation of Gonzalez Prada, the others became a matter of reflection and Andean peasants began to appear as characters of literary pieces. Palma works and his personal testimony were taken into account to study the literary process, as well as the writings of Mercedes Cabello about the literary trends of her time. The role of the government towards intellectual life, especially during the mid-nineteenth century has also been considered.